2013
DOI: 10.1155/2013/256060
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of Occupational Noise Exposure on Blood Pressure and Heart Rate of Steel Industry Workers

Abstract: Background and Objectives. This study aimed to investigate the effect of noise exposure on blood pressure and heart rate of steel industry workers. Materials and Methods. In the present cross-sectional study, 50 workers were selected from a steel company in Fars province, Iran, and exposed to 85, 95, and 105 dB noise levels for 5 minutes. The participants' blood pressure and heart rate were measured using Beurer BC16 pulse meter both before and after the exposure. Results. The study results showed no significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 2 publications
1
18
0
3
Order By: Relevance
“…Results of such studies are mixed. For blood pressure, while Lee et al (2010) found no changes across noise exposed groups, Lusk et al (2004) and Zamanian et al (2013) observed increased blood pressure with noise exposure. Likewise, Bjor et al (2007) found no changes in HRV between noise exposure groups; however, both Lee et al (2010) and Kraus et al (2013) found significant changes in HRV in groups exposed to higher noise intensities.…”
Section: 1 Introductionmentioning
confidence: 80%
“…Results of such studies are mixed. For blood pressure, while Lee et al (2010) found no changes across noise exposed groups, Lusk et al (2004) and Zamanian et al (2013) observed increased blood pressure with noise exposure. Likewise, Bjor et al (2007) found no changes in HRV between noise exposure groups; however, both Lee et al (2010) and Kraus et al (2013) found significant changes in HRV in groups exposed to higher noise intensities.…”
Section: 1 Introductionmentioning
confidence: 80%
“…Similarly, according to research by Zamanian et al 23 which examined the effect of steel industry noise exposure with the intensity of 85, 95, and 105 dBA for 5 minutes to blood pressure and heart rate in 50 industrial workers in Iran. The results showed that with 5 min exposure there was an increase in blood pressure however it was statistically insignificant.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that with 5 min exposure there was an increase in blood pressure however it was statistically insignificant. 23 Kalantary et al 12 stated that significant differences in blood pressure (systolic and diastolic) between the unexposed groups (exposure to 53 dBA noise) and exposed group (exposed to noise 85-108 dBA occurred. The results of this study are also in line with the research of Chen et al 24 which stated exposure to the noise intensity of 87.5 dB (A), the duration of noise exposure of 4.21 years and a CNE of 92.28% increased systolic and diastolic blood pressure of labors.…”
Section: Discussionmentioning
confidence: 99%
“…Em vigência de exposição ao ruído, verificou-se aumento da pressão arterial sistólica em trabalhadores de uma empresa siderúrgica em Fars, Irã. Contudo, não se confirmou resultado significativo (p > 0,05) quando os índices pressóricos foram comparados com a situação anterior à exposição 27 . Em um estudo transversal que focalizou amostra probabilística de 4.300 motoristas rodoviários da cidade de Isfahan, Irã, a pressão arterial não apresentou significância estatística com a perda auditiva induzida por ruído 21 .…”
Section: Discussionunclassified